New Evidence for the Timing of Arctic Small Tool Tradition Coastal Settlement in Northwest Alaska - Tremayne, Andrew (2016)
This paper presents the results of a survey of the oldest beach ridges located on Cape Espenberg in Bering Land Bridge National Preserve, Alaska. The goals were to locate and test Arctic Small Tool tradition (ASTt) sites to develop a coastal settlement chronology and to establish whether marine resources were exploited. At the outset of this project four ASTt sites were known at Cape Espenberg, two with associated radiocarbon dates. Upon completion, ten new ASTt sites with eleven radiocarbon dates were added to the record. Analysis of the radiocarbon dates indicate ASTt occupations at Cape Espenberg began at least 4,500 years ago and lasted a millennium. Comparisons among ASTt sites throughout Alaska suggest the coast was settled prior to the interior. The site designated KTZ-325 yielded the oldest securely dated evidence for sea mammal use in Northwest Alaska, supporting the hypothesis that ASTt people had a maritime economy in place at the start of their florescence in Alaska and beyond.